Misconceptions of biology education students in Biochemistry Course during the COVID-19 pandemic - Poncojari Wahyono; Eko Susetyorini (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Misconception is one of the main problems in biology education which has the potential to increase when course is packaged in a e-learning. This study aimed to map the level of the biochemistry concept accuracy of students who take online biochemistry lectures. This quantitative research involved Biology Education students, FKIP UMM as research subjects. Online lectures were conducted for ten meetings using ELMU UMM. At the 11st meeting, a concept accuracy test was carried out. The data were then analyzed using descriptive statistics. The result, 64% of students have a low level of concept accuracy, 14% moderate, and 0% good. Therefore, online learning packaging needs to be optimized so that the percentage accuracy of the biochemical concepts of students is maximized.